Content of nutritionally important components in mare milk fat - Pavlína Navrátilová; Jan Pospíšil; Ivana Borkovcová; Lenka Kaniová; Sandra Dluhošová; Simona Horáková (Mljekarstvo)
Characteristic properties that make mare milk interesting from a nutritional point of view, include the different composition and properties of milk fat. The aim of this study was to determine the total fat content, cholesterol content, percentage of saturated fatty acids (SFA), monounsaturated (MUFA) and polyunsaturated fatty acids (PUFA), content of n-3 and n-6 PUFA, linoleic acid (LA) and alpha-linolenic acid (ALA) in milk samples obtained from 10 mares during the first 6 months of lactation. Content of fat (9.79±7.04 g/L) and cholesterol (27.47±14.72 mg/L) in mare milk was lower than in human and bovine milk. From the nutritional point of view, the higher percentage of unsaturated FA (55 %) was significant, while MUFA represented 34 % and PUFA 21 % of that. The proportion of essential fatty acids of LA and ALA was 12.3 % and 3.9 % respectively. The ratio of n-6/n-3 PUFA was the most balanced in the first half of lactation. The influence of breed, stage of lactation and feed was statistically evaluated. The milk fat composition exhibited relatively large variability depending on these factors. Milk was richer in nutritionally important ingredients during the first three months of lactation.